The Effect of Music Therapy on Adult Patients’ Heart Rate: A Meta-Analysis - Kamila Alammar; Omar Ghazi Baker; Areej Alotaiba; Amwar Alkhunaizi (Nurse Media Journal of Nursing, 2022)
Background: Music can be used as a complementary intervention to bring about a positive effect on the quality of life. It has been widely employed in clinical practice as one of the earliest forms of treatment. Despite the fact that music therapy is widely utilized and practiced in clinical and educational contexts, it has received little attention in formal medical settings. In addition, contradictory findings about the effect of music deserve further investigation.Purpose: This meta-analysis is conducted to examine the effect of music therapy on heart rates among adult patients.Methods: The MEDLINE, CINAHL, PsycInfo, Cochrane Library, and PubMed databases were used for searching the literature. The literature review was conducted by two independent researchers using the following Medical Subject Headings terms: musicotherapy OR music therapy, AND heart rate OR vital signs AND clinical trials as the topic. Standard mean difference (SMD) with 95% confidence interval (CI) values was used to evaluate the effect of music therapy on heart rates.Results: Out of 194 studies, 12 studies were included with 1,118 patients. According to the results of the meta-analysis, the heart rates in the experimental groups in which music therapy was used with various diagnoses of adult patients were found to be significantly different in comparison with the control group (SMD=-0.450, 95% CI=-8.86 to -0.31, p=0.04).Conclusion:The results established that using music therapy for adult patients reduced their heart rates. However, the heterogeneity among the studies was high. Therefore, it is recommended that high-quality trials are warranted to confirm the benefits of music therapy interventions among adult patients.